Assessment of Na2SiO3 to NaOH ratio impact on the performance of polypropylene fiber-reinforced geopolymer composites. (20th October 2018) - Mohseni, Ehsan
Highlights: Increasing the monomer ratio enhanced the compressive strength. Increasing the fibres improved the flexural strength. The higher Si/Al ratio, the higher compressive and flexural strength. By increasing the monomer ratio, the durability improved dramatically. Density of polymer products developed in the presence of suitable monomer ratio. Abstract: The aim of this project is to build and use a concrete with minimum irritating impacts on the environment, reasonable price and optimal properties. Geopolymer concrete is new class of mineral binder that due to the high durability, very low energy consumption, very low CO2 emission, low investment cost and also special properties, is distinguished of other mineral binder such as Portland cement. In this study, after construction of metakaolin-based geopolymer concrete containing 0.3, 0.5 and 1% polypropylene (PP) fibers with monomer ratios of 2, 2.5 and 3, engineering properties including compressive strength, flexural strength, displacement, Si/Al ratio, water absorption and electrical resistivity were assessed. Microstructural and structural changes of geopolymers as a result of lead addition/immobilization were evaluated via scanning electron microscopic (SEM) and X-ray Diffraction (XRD) tests. The obtained results showed that using PP fiber in geopolymer samples increased the flexural strength by 28%. Furthermore, as evidenced by XRD diffractogram, the compressive strength improved by increasing the SS/SH ratio due to the formation of crystalline nepheline in the geopolymer specimens. In addition, images of electron microscopy of hardened geopolymer paste confirmed the remarkable increase in the density and uniformity of polymer products in the presence of suitable monomer ratios. In general, it is reported that using 1% PP fibers along with the sodium silicate to sodium hydroxide ratio of 3 had an acceptable outcome in improving geopolymer concrete performance from point of view of environmentally, structurally and economically.